2023
DOI: 10.1021/acsami.3c06363
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Semiconductor SERS Activity: The Impact of the Defect-Induced Energy Band Offset and Electron Lifetime Change

Yinghao Xu,
Renli Chen,
Shenlong Jiang
et al.

Abstract: The significant boost in surface-enhanced Raman scattering (SERS) by the chemical enhancement of semiconducting oxides is a pivotal finding. It offers a prospective path toward high uniformity and low-cost SERS substrates. However, a detailed understanding of factors that influence the charge transfer process is still insufficient. Herein, we reveal the important role of defect-induced band offset and electron lifetime change in SERS evolution observed in a MoO 3 oxide semiconductor. By modulating the density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…In Figure a, the signal at around 1380 cm –1 of 2-NTT was distinctly amplified on the Au NP-based substrates. The enhancement factor (EF) of Au NPs@PSA200- b -PMA was calculated as 9.38 × 10 6 , which was comparable to the other SERS studies. Due to the electromagnetic mechanism of Au NPs, the limit of detection for 2-NTT on Au NPs@PSA200- b -PMA was estimated to be 10 –7 M (Figure S19). In addition, the SERS performance of Au NPs of different sizes was explored.…”
supporting
confidence: 76%
“…In Figure a, the signal at around 1380 cm –1 of 2-NTT was distinctly amplified on the Au NP-based substrates. The enhancement factor (EF) of Au NPs@PSA200- b -PMA was calculated as 9.38 × 10 6 , which was comparable to the other SERS studies. Due to the electromagnetic mechanism of Au NPs, the limit of detection for 2-NTT on Au NPs@PSA200- b -PMA was estimated to be 10 –7 M (Figure S19). In addition, the SERS performance of Au NPs of different sizes was explored.…”
supporting
confidence: 76%
“…When the excited electron recovers from the CB to the defect level near the middle of band gap and is then re-excited by another photon, the resonance charge transfer between the LUMO and defect levels (Process 1) occurs. 40 However, the constant downward movement of the defect levels might disrupt the resonance transfer and then degrade the SERS performance (Process 2).…”
Section: Resultsmentioning
confidence: 99%
“…The CM effect of semiconducting materials like TiO 2 , ZnO, MoS 2 , WSe 2 and MoO 3 has been extensively reported. 13–18 Practically, the SERS performance contributed by the CM is enhanced by regulating the defect density or levels to match the orbital energy levels of the adsorbed molecules, and boost the charge transfer efficiency. 19–21 For example, Cong et al reported impressive SERS performance measured on W 18 O 49 nanowires prepared by the hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%